The Form of Officer of Land Deed Officer (PPAT) in Distribution of Rights to Land Joint Assets Post Divorce - Putu Ayu Sriasih Wesna; I Made Suwitra; Putu Wira Atmaja (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2023)
The distribution of land rights to joint assets after the divorce needs to use a deed made by PPAT, because basically PPAT is a Land Deed Maker Official whose main task is to carry out some land registration activities by making a deed as evidence that a legal action has been taken regarding land rights or property rights. For the Flats Unit, which will be used as the basis for the registration of changes in land registration data caused by the legal act. The type of research used is normative legal research, with a research approach to legislation and concepts. Legal materials consist of primary and secondary legal materials. The analytical method used is description, evaluation, argumentation and interpretation. The deed of collective agreement can be used as the basis for entering the name of the ex-wife or ex-husband that has not been recorded in the certificate due to joint ownership which must be divided due to divorce as stated in PP 24 of 1997 Article 37 paragraph (2) regarding land registration. As long as the head of the national land agency office judges that the truth is sufficient, it can be implemented, because the National Land Agency is a government institution that has discretionary authority as stated in Act No. 30 of 2014 concerning government administration. From the names that have emerged between the ex-husband and the ex-wife, the process of Sharing Joint Rights is carried out using the APHB Deed (Deed of Sharing Joint Rights) made by PPAT.